2021
DOI: 10.3390/medicina57121311
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis Bone Complication after Active COVID-19 Infection: Preliminary Results

Abstract: Background and objectives: The course of SARS-CoV-2 (COVID-19) is still under analysis. The majority of complications arising from the infection are related to the respiratory system. The adverse effect of the viral infection on bone and joint tissue has also been observed. Materials and Methods: We present a group of 10 patients with degeneration of large joints and adjacent epiphyses of long bones and the spine, with a background of bone infarctions and avascular necrosis (AVN) immediately after infection wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 25 publications
(37 reference statements)
0
33
0
5
Order By: Relevance
“…Of these proposed mechanisms, a hypercoagulable state in itself has been documented to be a risk factor for the development of osteonecrosis 18 . From their case series of 10 patients, Sulewski et al concluded that COVID-19 infection alone might represent a risk factor for the development of osteonecrosis of the femoral head 19 . Symptomatic osteonecrosis of the knees has also been reported in patients who have recovered from COVID-19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these proposed mechanisms, a hypercoagulable state in itself has been documented to be a risk factor for the development of osteonecrosis 18 . From their case series of 10 patients, Sulewski et al concluded that COVID-19 infection alone might represent a risk factor for the development of osteonecrosis of the femoral head 19 . Symptomatic osteonecrosis of the knees has also been reported in patients who have recovered from COVID-19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be this prothrombic state that led to a veno-occlusive state in our patient. There are only a small number of case reports with similar findings of femoral AVN following a COVID-19 infection [6]. Only two of those showed bilateral AVN and none with such delayed presentation resulting in bilateral femoral neck fractures [7].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with systemic lupus erythematosus (SLE), solid organ transplants, hematological diseases, multiple sclerosis, and recent neurosurgery have higher prevalence of steroid induced osteonecrosis [ 49 ]. Severe acute respiratory syndrome and SARS-CoV-2 infections (i.e., COVID-19) also puts patients at risk for developing osteonecrosis [ [49] , [50] , [51] , [52] ]. In one study in SLE, a prednisone-equivalent dosage greater than 30–40 mg/daily or a cumulative dose ≥12 g/year conferred a significant risk of osteonecrosis while in patients undergoing kidney transplantation, the dose of systemic glucocorticoids in the first weeks was more important than the total cumulative dose.…”
Section: Risk Factorsmentioning
confidence: 99%